2022
DOI: 10.1101/2022.06.13.22276366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitochondrial MICOS complex genes, implicated in hypoplastic left heart syndrome, maintain cardiac contractility and actomyosin integrity

Abstract: Hypoplastic left heart syndrome (HLHS) is a severe congenital heart disease (CHD) with a likely oligogenic etiology, but our understanding of the genetic complexities and pathogenic mechanisms leading to HLHS is limited. We therefore performed whole genome sequencing (WGS) on a large cohort of HLHS patients and their families to identify candidate genes that were then tested in Drosophila heart model for functional and structural requirements. Bioinformatic analysis of WGS data from an index family comprised o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“… 171 , 185 Rare variants in MIC19 and MIC25 are associated with hypoplastic left heart syndrome. 193 Consistent with a causal role, depletion of Mic19 in the Drosophila heart compromises heart function, decreases ATP, and results in the accumulation of mitochondrial aggregates, suggestive of altered mitochondrial dynamics. 193 In mammals, knockout of either MIC10 or MIC60 results in a reduction in maximal mitochondrial respiration.…”
Section: Cristae Dynamics and The Micos Complex In Hfmentioning
confidence: 88%
See 1 more Smart Citation
“… 171 , 185 Rare variants in MIC19 and MIC25 are associated with hypoplastic left heart syndrome. 193 Consistent with a causal role, depletion of Mic19 in the Drosophila heart compromises heart function, decreases ATP, and results in the accumulation of mitochondrial aggregates, suggestive of altered mitochondrial dynamics. 193 In mammals, knockout of either MIC10 or MIC60 results in a reduction in maximal mitochondrial respiration.…”
Section: Cristae Dynamics and The Micos Complex In Hfmentioning
confidence: 88%
“… 193 Consistent with a causal role, depletion of Mic19 in the Drosophila heart compromises heart function, decreases ATP, and results in the accumulation of mitochondrial aggregates, suggestive of altered mitochondrial dynamics. 193 In mammals, knockout of either MIC10 or MIC60 results in a reduction in maximal mitochondrial respiration. 171 , 173 , 185 However, it is not known whether there are differences in MICOS complex expression across different types of HF (Figure 1 ) or whether only certain MICOS complex subunits are essential for stability in HF.…”
Section: Cristae Dynamics and The Micos Complex In Hfmentioning
confidence: 88%
“…The role of the MICOS complex in disease states remains more controversial. Generally, loss of the MICOS complex has been shown to reduce cardiac ATP levels, thus impairing tissue integrity 95 . Studies within other tissue types, such as the liver have shown that Chchd3 depletion results in impaired MERCs to induce fatty liver disease with SLC25A46 involvement 96 .…”
Section: Discussion: Structural Analysismentioning
confidence: 99%
“…PRKCI is required for heart trabeculation in mice (57), PIK3R2 regulates heart size and hypertrophy in mice (58), PIK3CB promotes CM proliferation and survival in neonatal rat CMs (59) and PRKCA regulates heart contractility in mice (60). In addition, the ERBB2 R599C receptor had reduced interaction with proteins such as SOS1, PTPN11, CBL, which have been associated with syndromic CHD (61, 62) (63) and MICOS13, DTNA, and EMC1 which have been associated with nonsyndromic CHD (64) (65, 66). In addition, the mutant receptor has lost interaction with FRS2, and Frs2alpha is required for outflow tract morphogenesis (67).…”
Section: Discussionmentioning
confidence: 99%